Replacing gamma knife beam‐profiles on film with point‐detector scans. Issue 3 (9th January 2022) - Rudek, Benedikt; Bernstein, Kenneth; Osterman, Sunshine; Qu, Tanxia
Abstract: Purpose: Detector arrays and profile‐scans have widely replaced film‐measurements for quality assurance (QA) on linear accelerators. Film is still used for relative output factor (ROF) measurements, positioning, and dose‐profile verification for annual Leksell Gamma Knife (LGK) QA. This study shows that small‐field active detector measurements can be performed in the easily accessed clinical mode and that they are an effective replacement to time‐consuming and exacting film measurements. Methods: Beam profiles and positioning scans for 4‐mm, 8‐mm, and 16‐mm‐collimated fields were collected along the x‐, y‐, and z‐axes. The Exradin W2‐scintillator and the PTW microdiamond‐detector were placed in custom inserts centered in the Elekta solid‐water phantom for these scans. GafChromic EBT3‐film was irradiated with single uniformly collimated exposures as the clinical‐standard reference, using the same solid‐water phantom for profile tests and the Elekta film holder for radiation focal point (RFP)/patient‐positioning system (PPS) coincidence. All experimental data were compared to the tissue‐maximum‐ratio‐based (TMR10) dose calculation. Results: The detector‐measured beam profiles and film‐based profiles showed excellent agreement with TMR10‐predicted full‐width, half‐maximum (FWHM) values. Absolute differences between the measured FWHM and FWHM from the treatment‐planning system were on average 0.13 mm, 0.08 mm, and 0.04 mm for film, microdiamond, and scintillator, respectively. The coincidence between the RFP and the PPS was measured to be ≤0.5 mm with microdiamond, ≤0.41 mm with the W2‐1 × 1 scintillator, and ≤0.22 mm using the film‐technique. Conclusions: Small‐volume field detectors, used in conjunction with a clinically available phantom, an electrometer with data‐logging, and treatment plans created in clinical mode offer an efficient and viable alternative for film‐based profile tests. Position verification can be accurately performed when CBCT‐imaging is available to correct for residual detector‐position uncertainty. Scans are easily set up within the treatment‐planning‐system and, when coupled with an automated analysis, can provide accurate measurements within minutes.